2014
DOI: 10.2174/1389202915999140404100958
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways Associated with Aggressiveness of Papillary Thyroid Cancer

Abstract: The most common thyroid malignancy is papillary thyroid cancer (PTC). Mortality rates from PTC mainly depend on its aggressiveness. Geno- and phenotyping of aggressive PTC has advanced our understanding of treatment failures and of potential future therapies. Unraveling molecular signaling pathways of PTC including its aggressive forms will hopefully pave the road to reduce mortality but also morbidity from this cancer. The mitogen-activated protein kinase and the phosphatidylinositol 3-kinase signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 116 publications
(112 reference statements)
0
22
0
Order By: Relevance
“…They regulate gene expression at the post-transcriptional level by binding to imperfectly complementary sequences within target mRNAs, often in the 3¢-untranslated regions, thereby leading to degradation or translational suppression (32). Although definitive studies are currently lacking, miRs may nevertheless have potential as prognostic indicators in PTC, thereby optimizing the surgical management of patients with PTC (28,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: V600ementioning
confidence: 99%
“…They regulate gene expression at the post-transcriptional level by binding to imperfectly complementary sequences within target mRNAs, often in the 3¢-untranslated regions, thereby leading to degradation or translational suppression (32). Although definitive studies are currently lacking, miRs may nevertheless have potential as prognostic indicators in PTC, thereby optimizing the surgical management of patients with PTC (28,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: V600ementioning
confidence: 99%
“…The recent expansion of knowledge and efforts to genetically characterize PTCs by The Cancer Genome Atlas Research Network (TCGA) Thyroid working group and others have revealed that microRNAs may play an important role in PTC prognosis (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). MicroRNAs (miR) are small non-protein coding RNA molecules that are 21-25 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that specific miRs are associated with aggressive clinicopathologic features of PTC, such as those listed above in addition to BRAF mutation. However, other studies failed to report any significant 4 4 association (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTC generally has an indolent course and favorable prognosis (9). However, there remain 20-30% of patients where PTC recrudesces and became resistant to radioactive iodine treatment, particularly in patients with advanced thyroid carcinoma, yielding poor prognosis and shorter survival (10,11). Therefore, there is an urgent requirement to elucidate the molecular mechanism underlying thyroid carcinoma progression and to improve the survival rate of patients with thyroid carcinoma.…”
Section: Introductionmentioning
confidence: 99%